Artificial Intelligence and Brain Rot: Implications for Students’ Cognitive Development and Character Education - Muhamad Slamet Yahya; Alwi Maulana; Khafifatul Fian (Yayasan Azhar Amanaa Yogyakarta, 2026)
The rapid integration of Artificial Intelligence (AI) into education has transformed students’ learning patterns, offering both cognitive opportunities and psychological challenges. This study explores the implications of AI on the phenomenon of brain rot a term referring to cognitive stagnation, reduced attention span, and diminished motivation caused by overexposure to shallow digital stimuli. Using a literature-based qualitative method, data were gathered from relevant academic sources, books, and online reports to analyze the dual impact of AI on students’ cognitive and motivational domains. The findings reveal that, while AI fosters personalized learning and enhances self-efficacy through adaptive systems and data-driven feedback, it simultaneously risks promoting intellectual passivity when students excessively rely on generative AI for instant answers. Such overdependence weakens analytical, evaluative, and creative abilities core components of higher-order thinking thereby accelerating symptoms of brain rot. The study further highlights that digital environments saturated with short-form content amplify these risks, conditioning students to seek immediate gratification and undermining their capacity for deep learning. However, when employed reflectively, AI can serve as a metacognitive scaffold that promotes inquiry, reflection, and sustained engagement. To mitigate the negative implications, the research emphasizes the necessity of integrating digital literacy, ethical awareness, and self-regulation into educational frameworks. In conclusion, AI should be positioned not as a cognitive substitute but as a supportive partner in learning one that enhances critical thinking and preserves intellectual vitality in the digital age.